2019
DOI: 10.1002/eat.23041
|View full text |Cite
|
Sign up to set email alerts
|

Comparing self‐harming intentions underlying eating disordered behaviors and NSSI: Evidence that distinctions are less clear than assumed

Abstract: Objective Eating disordered (ED) behaviors (i.e., binge eating, compensatory behaviors, restrictive eating) and nonsuicidal self‐injury (NSSI; intentional and nonsuicidal self‐harm) are highly comorbid and share several similarities, including consequent pain and physical damage. However, whereas NSSI is considered direct self‐harm, ED behaviors are considered indirect self‐harm. These distinctions stem from theoretical understanding that NSSI is enacted to cause physical harm in the moment, whereas ED behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
44
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 55 publications
6
44
0
2
Order By: Relevance
“…concert with previous research byFox et al (2019), suggest one possible reason for the stronger association between suicidal ideation and restrictive eating (compared to binge eating/purging) may be self-harming and suicidal motivations underlying restrictive eating behaviors.Limitations of this study include the cross-sectional design, as well as relatively small sample size of only females in a limited age range. Because the sample was recruited based on low weight, more participants endorsed fasting than binge eating and purging, and these smaller numbers may have limited our ability to detect statistically significant associations of these behaviors with suicidal ideation.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…concert with previous research byFox et al (2019), suggest one possible reason for the stronger association between suicidal ideation and restrictive eating (compared to binge eating/purging) may be self-harming and suicidal motivations underlying restrictive eating behaviors.Limitations of this study include the cross-sectional design, as well as relatively small sample size of only females in a limited age range. Because the sample was recruited based on low weight, more participants endorsed fasting than binge eating and purging, and these smaller numbers may have limited our ability to detect statistically significant associations of these behaviors with suicidal ideation.…”
supporting
confidence: 79%
“…Although ED behaviors are typically conceptualized as functioning to control weight/shape, emerging research suggests individuals also engage in these behaviors with at least some intention to hurt themselves physically in the moment and in the long run (Fox et al, ). Notably, compared to binge eating and purging, individuals report restricting with a greater intent to cause long‐term physical harm, a higher hope and knowledge of dying sooner as a consequence of restrictive eating, and greater thoughts of restricting to kill oneself (Fox et al, ). Although the current study did not assess motivations underlying fasting beyond controlling shape/weight, our findings, considered in concert with previous research by Fox et al (), suggest one possible reason for the stronger association between suicidal ideation and restrictive eating (compared to binge eating/purging) may be self‐harming and suicidal motivations underlying restrictive eating behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, BPB may also increase risk for onsets of other mental health problems (e.g., Riley, Davis, Combs, Jordan, & Smith, ). In addition, the comorbidity with NSSI/suicidal behaviors has been reported in eating disorder patients, as these behaviors may be functionally equivalent within the self‐harming spectrum (Claes & Muehlenkamp, ; Fox et al, ). Taken together, our data are consistent with the thought that BPB represent a behavioral marker of psychopathological distress among incoming college students.…”
Section: Discussionmentioning
confidence: 99%
“…Nonsuicidal self-injury (NSSI), deliberately self-inflicted bodily harm without suicidal intent, frequently co-occurs with disordered eating patterns [1]. A recent meta-analysis found that over 27% of patients diagnosed with eating disorders (EDs) endorsed a lifetime history of NSSI [2], and conversely, up to 55% of individuals who engage in NSSI report some disordered eating activities [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…These proposed categories refer to the distinct temporal relationships between different self-injurious behaviors and resulting physical harm as well as the extent to which that harm is intentional; NSSI was originally conceptualized as unique from ED behaviors in that physical harm is both immediate and deliberate. However, recent work suggests that both forms of self-injury can involve a desire to cause physical damage to oneself in the moment and over time, in addition to some degree of suicidal ideation [1].…”
Section: Introductionmentioning
confidence: 99%